Reward-based crowdfunding success: decomposition of the project, product category, entrepreneur, and location effects - CHAN, C. S. Richard (Institutional Knowledge at Singapore Management University, 2018)
We assess the relative importance of project, product category, entrepreneur, and location effects on reward-based crowdfunding success. Applying variance decomposition analysis to a sample of 98,336 crowdfunding projects launched between May 2009 and May 2014 on the Kickstarter platform, we find that agency factors, specifically the project and entrepreneur effects, explain the highest relative variance (over 80% of total variance) across three crowdfunding success outcomes – pledge amount, number of backers, and funding success. Structural factors, specifically product category and location effects, have lower but still significant effects. Our study extends prior variance decomposition studies in strategy and entrepreneurship research by incorporating location effects and examining the nascent stage of firm formation. It also contributes to crowdfunding research by providing a systematic framework to compare key determinants of reward-based crowdfunding outcomes. The findings are of practical relevance to aspiring entrepreneurs seeking funding through reward-based crowdfunding platforms.